Jaminan dan Fasilitas terhadap Kepuasan Pelanggan - Saparudin Saparudin (Journal of Management and Bussines (JOMB), 2021)
This study aims to determine the effect of guarantees and facilities on customer satisfaction either partially or simultaneously. The sample in this study was 53 people with a sampling method that was accidental sampling. The analytical method used is a quantitative analysis using the SPSS program. The result of this research is testing the effect of the Assurance variable (X1) on Customer Satisfaction (Y), obtained a Sig value of 0.000 <0.05. They are trying the influence of the Facility variable (X2) on Customer Satisfaction (Y) Sig 0.017 <0.05. The conclusions obtained are as follows: a) Assurance variable (X1) has a significant effect on Customer Satisfaction (Y); b) The Facility Variable (X2) has a significant effect on the Customer Satisfaction variable (Y); c) Assurance variable (X1), and Facility (X2) have a significant effect together on the Customer Satisfaction variable (Y). Keywords: Facilities, Guarantee, Customer Satisfaction